2020
DOI: 10.3145/epi.2020.sep.29
|View full text |Cite
|
Sign up to set email alerts
|

The Media pluralism monitor: Conceptualizing media pluralism for the online environment

Abstract: Media pluralism is an essential feature and pillar of contemporary democracies. It is a corollary of the right to freedom of expression, as guaranteed by European national constitutions, as well as by the Convention for the protection of human rights and fundamental freedoms (art. 10) and by the Charter of fundamental rights of the European Union (art. 11). Ensuring a plural media environment is a precondition for democracy and may be seen as a policy goal. The availability and accessibility of diverse informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Considering the development of democracy, not only is it important to maintain the freedom of expression of individuals and groups, but it is also important to ensure that such groups have the opportunity to comprehensively and accurately present their opinions to the public. Here, we discuss the relevance of media pluralism for the functioning of democracy (Ciaglia, 2013;Karppinen, 2013;Brogi and Parcu, 2014;Brogi, 2020). In light of this, we conclude that the political life of democratic polity needs a diversified media space consisting of media outlets (newspapers and radio and television networks) that are receptive to viewpoints of different political and ideological orientations.…”
Section: Methodsmentioning
confidence: 92%
“…Considering the development of democracy, not only is it important to maintain the freedom of expression of individuals and groups, but it is also important to ensure that such groups have the opportunity to comprehensively and accurately present their opinions to the public. Here, we discuss the relevance of media pluralism for the functioning of democracy (Ciaglia, 2013;Karppinen, 2013;Brogi and Parcu, 2014;Brogi, 2020). In light of this, we conclude that the political life of democratic polity needs a diversified media space consisting of media outlets (newspapers and radio and television networks) that are receptive to viewpoints of different political and ideological orientations.…”
Section: Methodsmentioning
confidence: 92%
“…The values assigned were as follows: total distrust = 1, less trust = 2, comparative trust = 3, and very trust = 4. Thereafter, the scores of three levels of government departments were added to form a continuous variable of [ 3 , 12 ]. The higher the score, the higher the degree of trust in the government.…”
Section: Methodsmentioning
confidence: 99%
“…A part of the literature suggests that higher frequency of Internet use results in lower environmental satisfaction among the public [ 2 ]. Owing to its pluralistic and autonomous characteristics [ 3 ], new media such as the Internet may result in the large-scale dissemination of negative environmental information, thereby amplifying people’s dissatisfaction with the current environment [ 4 ]. Porumbescu surveyed 1100 Seoul citizens and revealed that Internet use reinforces the negative relation between public expectations of public sector performance and satisfaction with public services.…”
Section: Introductionmentioning
confidence: 99%
“…Most frequently, media pluralism, in this case external, is associated with the diversity and transparency of media ownership where increased market accumulation can result in the development of monopoly and oligopoly (Brogi, 2020). In addition, it can threaten the democratic debate by narrowing the media space for different opinions and attitudes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In that way, many users of digital information remain deprived of different points of view, attitudes and opinions, which is limiting their participation in a democratic spirit. In order to overcome the discovered inadequacies and improve the conditions for the development of media pluralism and plurality of information, algorithms should be developed in a way that exposes users to a variety of information of public interest, and not just to personalized and/or popular content (Brogi, 2020;Helberger, 2015). Also, other authors have expressed similar thoughts.…”
Section: Theoretical Frameworkmentioning
confidence: 99%